2015
DOI: 10.1016/j.phytochem.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of small molecule inhibitors of xyloglucan endotransglucosylase (XET) activity by high-throughput screening

Abstract: Graphical abstractXenobiotics that inhibit the cell-wall-remodelling enzyme activity, xyloglucan endotransglucosylase (XET), would be a valuable tool in ‘chemical genetics’ for elucidating its biological roles. By screening 4216 small molecules in a dot-blot assay on paper-immobilised xyloglucan, we discovered 45 compounds that inhibited or promoted XET activity. The most effective inhibitors were singlet oxygen generators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…1 O 2 is produced by riboflavin (in the presence of air containing ordinary oxygen, 3 O 2 ) in the light but not in the dark [ 40 , 70 , 85 ], so samples incubated with riboflavin in the dark or without riboflavin in the light serve as ROS-free controls. 1 O 2 production from 3 O 2 by riboflavin in the light is not stoichiometric: each riboflavin molecule can generate many 1 O 2 molecules, although the yield is not unlimited because riboflavin itself is subject to oxidation by 1 O 2 [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 O 2 is produced by riboflavin (in the presence of air containing ordinary oxygen, 3 O 2 ) in the light but not in the dark [ 40 , 70 , 85 ], so samples incubated with riboflavin in the dark or without riboflavin in the light serve as ROS-free controls. 1 O 2 production from 3 O 2 by riboflavin in the light is not stoichiometric: each riboflavin molecule can generate many 1 O 2 molecules, although the yield is not unlimited because riboflavin itself is subject to oxidation by 1 O 2 [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…in the presence of tryptophan; [ 37 , 38 ]) and visible light (e.g. in the presence of riboflavin; [ 39 , 40 ]), and has been reported to be responsible for the majority of photo-oxidative damage in leaves [ 41 ]. • OH is the most potent but also the shortest-lived ROS [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a screen for inhibitors of xyloglucan endotransglucosylation reported the reduction of parsley XET activity by BB-R250 [19]. We found that BB-R250 also reduced the XET activity in enzyme extracts prepared from host-invading haustoria of C .…”
Section: Resultsmentioning
confidence: 71%
“…Numerous phenotypic screens for small molecule inhibitors of cell wall biosynthesis have been conducted, and have identified a variety of cellulose biosynthesis inhibitors [ 34 37 ]. Small molecule inhibitors of xyloglucan endo-transglycosylase have also been identified [ 38 ]. However, these molecules are structurally diverse, precluding the facile identification of a direct target.…”
Section: Introductionmentioning
confidence: 99%